Reforming the imagination - Major, R; Major, R. J. C. (1991)
﻿ This is a study of some literary aspects of English thinking during the eighty years from Elizabeth's Settlement of religion to the Civil Wars. The central thesis is that there is a shift in the images the English Protestant mind uses for its own acquisition of knowledge: from images of public and visible entities, lit by the ubiquitous sunlight of authority and reason, to images of direct cognisance by the self, lit by internal Promethean light. As this image of inner light is primarily an image of reading, there is an imaginative, and thus exegetical, identification of the inspired reader with the meaning or Voice' within the text. This identification is exploited by the more radical Protestants, the party in favour of further reform, to rebut the negative aspersions of scepticism, and the positive aspersions of Catholic polemic; especially in poetry that means to vindicate the truths of Protestant dogma, which is notionally read from the Bible, by replicating and extending the experience of inspired reading. Protestants are ambivalent about the legitimacy of such 'divine' literature, but nevertheless Nosce teipsum, New Atlantis, Sidney's Arcadia, Paradise Lost and even Robinson Crusoe are shown to employ this Protestant mode of inspired defence. In the first of three parts, English Reformation uses of the word imagination are distinguished, and the Protestant faculty of inspiration is shown to be a function of the secondary imagination. Part II discusses the Protestant ambivalence about human artifice on the edge of Scripture; such artifice is necessary to make the Bible work as Protestantism wants, but its existence compromises the Bible's character as a self-sufficient and self-interpreting oracle. This dilemma is demonstrated in the actions of English iconoclasm, and in English attitudes to illustrations of the Bible, Bible translation, and authoritative exegesis. In Part III, this same ambivalence is apparent in the theory and practice of literature, as evidenced by the writings of Jewel, Whitaker, Sidney, Greville, Hooker, Bacon, Sir John Davies, and Milton.